The Relaxed Tutorial Project: distance learning and anxiety in Classical Studies - Cora Beth Fraser; Naoko Yamagata; Ardle Mac Mahon (The Journal of Classics Teaching)
‘Relaxed’ events are now common across the public Arts and Heritage sectors. Although designed with the needs of autistic children and their families in mind, they suit people with a range of access needs. Our project at The Open University asked: what would a ‘relaxed tutorial’ look like, and who might benefit from it? Across two years (2021–2023), tutors in the Department of Classical Studies at The Open University trialled a set of autism-friendly accessibility adjustments to live online tutorials for distance learners on a Roman History module. We found that relaxed tutorials were welcomed by students with anxiety disorders, caring responsibilities, chronic conditions and low confidence, as well as by autistic students. Since the project was concluded in 2023, relaxed tutorials have been rolled out across further Classical Studies modules at The Open University. Their principles and structure offer a new way of looking at accessibility adjustments which could be adapted to other teaching contexts and levels.